The Practice of Paradiplomacy in Cooperation between the Yogyakarta Special Region Government and the Singapore International Foundation in the Education Sector - Eva Yusnita Chandra; Dyah Estu Kurniawati (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political Social UMA), 2022)
This article aims to find out how the collaborative practices that occur between the Provincial Government of the Special Region of Yogyakarta (DIY) and the Singapore International Foundation (SIF) in the field of education. DIY is a province known as the "City of Education", but in reality, there are still several layers of society that need attention in terms of education, especially since the level of reading literacy is still low. Therefore, it is important to know the cooperation between DIY and SIF in the field of education, which focuses on increasing reading literacy in DIY. This study uses a qualitative descriptive method by taking data from the official websites of SIF and DIY, as well as news websites and related journal articles. The concept of Paradiplomacy is used in this study to describe the cooperation between DIY and SIF and its relation to international relations. The results obtained in this study are Word on Wheels (WoW) is the implementation of paradiplomacy practices between sub-state actors, which is DIY and SIF in the field of education. WoW aims to increase literacy in the community, especially among schoolchildren. During the 3 years this collaboration has been running, it has succeeded in contributing to increasing the Reading Literacy Activity Index (Alibaca) in DIY.